Knowledges from the South: Reflections on Writing Academically - Loncon-Antileo, E (Routledge, 2022)
In this paper, we dialogue about the processes of knowledge construction that work through and disrupt academic regulations. As feminist, Indigenous, and non-Indigenous Latinx scholars, we build on the reflections stemming from our research of Mapuche women s biographies of schooling. We focus on three tensions of knowledge production within and beyond academic spaces. First, we explore how the knowledges (in plural) that come from our biographies are systematically left out of academic conversations and moved into what we call invisible zones. Second, we examine the work of translation and translanguaging as we move across language barriers and geographic places in our research, which points to what these processes afford across geographic and conceptual zones of “north” and “south.” Thirdly, we unsettle the naturalized understanding of knowledge as solely a product of academic spaces and gesture toward a future in which we can reimagine and display complex and complicated ways of doing research otherwise. © 2022 American Educational Studies Association.